Above Ground Biomass and Carbon Stock Mapping using NDVI and Ecological Studies of Woody Trees of Jeypore Reserve Forest, Assam, India - Hussain, Tanvi; Devi, Haobam Suchitra; Sarma, Kamini Kanta (Indian Forester, 2019)
Jeypore Reserve Forest of eastern Assam is one among the few remaining tropical forest patches, lying in the fringe of Assam-Arunachal Pradesh state border. Role of tropical forests in global biogeochemical cycles, especially the carbon cycle and its relation to the greenhouse effect, has heightened interest in estimating the biomass density of tropical forests. A field survey on this forest using 60 sample points of 100m Ã— 100m dimension showed that remote sensing can provide information critically required for AGB and carbon stock assessment of the woody trees. The study was carried out with the aim to prepare AGB and carbon stock map of the forest using NDVI and to study the species richness, species diversity and IVI of the forest. Upon plotting NDVI values generated from Resourcesat-2 IRS P6 LISS III image and against AGB values it showed a rising trend, exponential curve was found to be the best fit. The regression equation derived was validated using 10 sample points and it was found that AGB values obtained from the field and obtained using the regression equation showed 98% correlation. Results of ecological studies revealed that Jeypore Reserve Forest have high species diversity of woody trees in scale of Shannon-Weaver index and IVI ranks Dipterocarpus retusus Blume as the most dominant species.